The ethical issues regarding consent to clinical trials with pre-term or sick neonates: a systematic review (framework synthesis) of the analytical (theoretical/philosophical) research - Megone, Chirstopher; Wilman, Eleanor; Oliver, Sandy; Duley, Lelia; Gyte, Gill; Wright, Judy (BioMed Central, 2016)
Background: Conducting clinical trials with pre-term or sick infants is important if care for this population is to be underpinned by sound evidence. Yet, approaching the parents of these infants at such a difficult time raises challenges to obtaining valid informed consent for such research. In this study, we asked, What light does the analytical literature cast on an ethically defensible approach to obtaining informed consent in perinatal clinical trials?